Jio and Google reveal the ultra-affordable JIOPHONE NEXT smartphone - Reliance Industries Limited (2022)
Jio and Google reveal the ultra-affordable JIOPHONE NEXT smartphone to empower millions of Indians with digital life, offered in their preferred language.